Answer:
a) Equation for spring constant k is
![k = (2E)/(e^2)](https://img.qammunity.org/2022/formulas/physics/high-school/jrifhsjz55udh1ntbxzeakp74in3lr18l7.png)
b)Equation for the extension squared is
![e^2 = (2E)/(k)](https://img.qammunity.org/2022/formulas/physics/high-school/9oe50y4b4g2mx3jw1exjk85n6h9smpjp6m.png)
(c) Equation for the extension e is
![e = \sqrt{(2E)/(k) }](https://img.qammunity.org/2022/formulas/physics/high-school/c1i83wq52x2ghfdnpo4zthjw29o7tx1mws.png)
Step-by-step explanation:
Given;
![E = (1)/(2) ke^2](https://img.qammunity.org/2022/formulas/physics/high-school/7vf2ndpd9pu9jtseatg48gkc0at9f7fgxy.png)
where;
E is the elastic potential energy
k is the spring constant
e is the extension of the spring
a) Equation for spring constant k is given as.
![E = (1)/(2) ke^2\\\\ke^2 = 2E\\\\k = (2E)/(e^2)](https://img.qammunity.org/2022/formulas/physics/high-school/z96yghvz8sro5novwutyldh5vowvvfpa29.png)
(b) Equation for the extension squared e2;
![E = (1)/(2) ke^2\\\\ke^2 = 2E\\\\e^2 = (2E)/(k)](https://img.qammunity.org/2022/formulas/physics/high-school/s9wses7d79bvg9ddes4lk8a7nj2nao02j7.png)
(c) Equation for the extension e;
![e^2 = (2E)/(k) \\\\e = \sqrt{(2E)/(k)}](https://img.qammunity.org/2022/formulas/physics/high-school/wra50zqio1avkk0100udbdu20mvsvwlfhz.png)